Singer Style - ugli, Ibrohimov Azizbek Ismonjon (International Journal on Human-Computing Studies, 2023)
in this article, phrases from the basics of singing, the origin of this style of singing and what affects them, the development of their voices and the necessary foundations for singers are analyzed in writing based on written sources.